Regulation and roles of mitophagy at synapses - Palikaras, K.; Tavernarakis, N. (Mech Ageing Dev, 2020)
Maintenance of synaptic homeostasis is a challenging task, due to the intricate spatial organization and intense activity of synapses. Typically, synapses are located far away from the neuronal cell body, where they orchestrate neuronal signalling and communication, through neurotransmitter release. Stationary mitochondria provide energy required for synaptic vesicle cycling, and preserve ionic balance by buffering intercellular calcium at synapses. Thus, synaptic homeostasis is critically dependent on proper mitochondrial function. Indeed, defective mitochondrial metabolism is a common feature of several neurodegenerative and psychiatric disorders, including Alzheimer's disease (AD), Parkinson's disease (PD), bipolar disorders and schizophrenia among others, which are also accompanied by excessive synaptic abnormalities. Specialized and compartmentalized quality control mechanisms have evolved to restore and maintain synaptic energy metabolism. Here, we survey recent advances towards the elucidation of the pivotal role of mitochondria in neurotransmission and implicating mitophagy in the maintenance of synaptic homeostasis during ageing.
Keywords: *Ageing; *Energy Metabolism; *Ionstasis; *Mitochondria; *Mitophagy; *neurodegeneration; *Neuron; *Plasticity; *Synapses; Animals; Humans; Mental Disorders/*metabolism/pathology; Mitochondria/*metabolism/pathology; Neurodegenerative Diseases/*metabolism/pathology; Neurons/*metabolism/pathology; Synapses/*metabolism/pathology; Synaptic Transmission